2009
DOI: 10.1136/bmj.b688
|View full text |Cite
|
Sign up to set email alerts
|

Total mortality after changes in leisure time physical activity in 50 year old men: 35 year follow-up of population based cohort

Abstract: Objective To examine how change in level of physical activity after middle age influences mortality and to compare it with the effect of smoking cessation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
222
2
12

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 263 publications
(263 citation statements)
references
References 52 publications
20
222
2
12
Order By: Relevance
“…Given the importance of taking into account changes in physical activity over time, 14,15 we used data on physical activity from phases 5 and 7 (N =7456) to constitute 3 participant groups. For the biggest group, composed of those who responded at both phases (n = 5549), data on physical activity at phase 5 were used for their contribution to the calculation of person-years until phase 7, and then data at phase 7 were used until either death or the end of follow-up on April 30, 2009.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the importance of taking into account changes in physical activity over time, 14,15 we used data on physical activity from phases 5 and 7 (N =7456) to constitute 3 participant groups. For the biggest group, composed of those who responded at both phases (n = 5549), data on physical activity at phase 5 were used for their contribution to the calculation of person-years until phase 7, and then data at phase 7 were used until either death or the end of follow-up on April 30, 2009.…”
Section: Discussionmentioning
confidence: 99%
“…1,15,20,21 Few studies have investigated the independent effects of the various levels of physical activity. 1,6 One study found moderately vigorous (MET ‡ 4.5) but not lower energetic activities to be associated with reduced risk of mortality 22 ; others compared vigorous and nonvigorous activities and showed that only vigorous activities were associated with reduced risk of mortality.…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%
“…Physical activity and good nutrition contribute to healthy ageing and reduces morbidity and mortality (79) . Physical activity has been shown to have protective effects against mortality in patients with chronic diseases such as CVD (80) .…”
Section: Physical Activity and Nutrition-based Interventionsmentioning
confidence: 99%
“…The time horizon was set at five years to allow stabilization of the beneficial effects from exercise or medical therapy. 10,11 Main outcomes used for comparison between strategies were death, MI, and complications from coronary angiography.…”
Section: The Decision Modelmentioning
confidence: 99%